Kripke semantics for Epistemic Logic of Relational Information between Ciphertexts - Hagihara, Shigeki (Philippine computing journal)
By configuring an adequate set of messages obtained by an adversary and analyzing the information which can be obtained by an adversary, it is possible to verify the secrecy of cryptography protocols. We have already proposed a deduction system for analyzing whether an adversary can obtain relational information between contents or keys of two ciphertexts are different...